Reconstruction after a major disaster: Lessons from the post-Tsunami experience in Indonesia, Sri Lanka, and Thailand - Sisira Jayasuriya; Peter McCawley (Asian Development Bank Institute (ADBI), 2008)
This paper examines several aspects of the rehabilitation and reconstruction program that followed the 2004 tsunami in Asia. Almost 230,000 people died in the disaster. We focus on two main issues: aid delivery and reconstruction policy following the disaster. Although issues such as immediate relief activities in disaster management and the role of political, institutional, and social factors in post-disaster recovery are also very important, they are not discussed in detail here. First, the effectiveness and financing of aid delivery arrangements following the tsunami are considered. The discussion aims to go beyond the headline figures on international aid to assess the level, composition, and quality of aid flows. Second, the challenges of designing reconstruction programs in the wake of the tsunami are surveyed. Questions of why there is often sharp escalation in construction costs and the implications for planning reconstruction are considered. These issues are often not discussed in the standard analytical literature about responses to disasters. It is argued that staggered disbursement of aid funds, although obviously highly undesirable in the case of urgent relief activities, may have benefits during the reconstruction phase by reducing inflationary pressures and leakage of aid funds. The pros and cons of alternative approaches are considered. Finally, it is suggested that a phased reconstruction program where the sequencing of activities is carefully prioritized will deliver better outcomes.
Keywords: F35; H54; O19; Q54; 330